2023
DOI: 10.1186/s12909-023-04158-8
|View full text |Cite
|
Sign up to set email alerts
|

Flipped classroom applied to Neurosurgery in undergraduate medical education

Abstract: Purpose To compare the academic achievement obtained in Neurosurgery in a class of undergraduate students according to the pedagogical methodology employed: flipped classroom (FC) versus traditional lecture. Students’ satisfaction with the FC model is also analyzed. Methods A quasi-experimental study was designed. The traditional lecture was the pedagogical method employed in teaching units (TUs) 1, 2, and 3 (61, 60, and 66 enrolled students, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…Flipped classrooms are beneficial in promoting performance. For instance, Gutierrez-Gonzalez et al (2023) utilised the flipped classroom in a neurosurgery lecture and found that students earned better academic results than in traditional lectures. W. Y.…”
Section: Flipped Classroommentioning
confidence: 99%
See 1 more Smart Citation
“…Flipped classrooms are beneficial in promoting performance. For instance, Gutierrez-Gonzalez et al (2023) utilised the flipped classroom in a neurosurgery lecture and found that students earned better academic results than in traditional lectures. W. Y.…”
Section: Flipped Classroommentioning
confidence: 99%
“…However, traditional teaching consists mainly of classroom lectures or video-supported teaching (Bartok-Nicolae et al, 2022) and usually involves less time to practise with assistance from the teacher in class (Hsia & Sung, 2020). In view of this, teachers have adopted the flipped learning approach, which reverses the sequence of teachers' lectures and learners' assignments (Gutierrez-Gonzalez et al, 2023). However, in the flipped learning approach, how to provide individual students with instant personalised guidance remains a challenging issue for teachers (Chang & Hwang, 2018).…”
Section: Introductionmentioning
confidence: 99%
“… 2 Current evidence demonstrates that the flipped classroom has advantages, mainly including higher theoretical knowledge scores and skill scores, over traditional teaching methods in various disciplines, such as nursing, 3 radiology, 4 pharmacy, 5 neurophysiology, 6 emergency, 7 dermatology, 8 cardiology 9 and neurosurgery. 10 Recently, an increasing number of studies have proposed and investigated the efficacy of the flipped classroom teaching model in anaesthesiology education, which also needs to provide extensive internal and surgical knowledge. 11–19 However, a systematic review and meta-analysis has not yet been conducted to determine the effectiveness of the flipped classroom teaching model among anesthesiology residents.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research into flipped classroom teaching methods in medical education have demonstrated advantages including improved student preparation [ 10 ], active participation, and the promotion of critical thinking skills, as well as disadvantages such as the need for student internet connection and inadequate student preparation [ 11 ]. As research on flipped learning in medical education continues to grow, there is a need to evaluate its impacts on student outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The flipped classroom has been applied in various medical subjects such as biology, physiology, haematology and pathology in higher education settings [ 14 ]. Empirical investigations in the field of medical education on the use of flipped classrooms, have shown a positive increase in students’ academic performance [ 15 – 18 ], satisfaction [ 10 , 19 21 ] and their engagement levels [ 22 ]. Recent meta-analysis of the effectiveness of the flipped classroom concluded that the approach resulted in a statistically significant improvement in learner performance compared with traditional teaching [ 23 ].…”
Section: Introductionmentioning
confidence: 99%